2022
DOI: 10.1186/s12912-021-00778-x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the views of operating room nurses and physicians on the relationship between professional values and professional communication

Abstract: Purpose Professional communication and professional values are two basic concepts in operating rooms and should be studied more closely in view of the nature of work and the high circulation of patients in operating rooms. Methods The present work is a descriptive-analytic study with a cross-sectional design. The sample was 603 operating room physicians and personnel selected from the public hospitals of Shiraz. The data collection instruments were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
(49 reference statements)
4
7
0
Order By: Relevance
“…, 2019). This finding is consistent with the extant literature, in which effective communication was one of the main components of safety culture in ORs (Yeganeh et al. , 2022).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…, 2019). This finding is consistent with the extant literature, in which effective communication was one of the main components of safety culture in ORs (Yeganeh et al. , 2022).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the extant literature, in which effective communication was one of the main components of safety culture in ORs (Yeganeh et al, 2022). The findings of this study confirmed that ineffective communication between OR professions about patient treatment and safety issues can heighten risk for patients and affected patients' safety (Yeganeh et al, 2022).…”
Section: Organizational Factorssupporting
confidence: 91%
See 3 more Smart Citations